Makna Atribut Istimewa pada Arca Perwujudan Tokoh-tokoh Perempuan Majapahit: Kajian Arkeologi Religi Hindu-Buddha - Nabila Mega Permata; Agus Aris Munandar; Evan Gavriel Harazaki (Center for Research and Development of Religious Literature and Heritage, 2022)
Attributes of the sculpture are one of the most important aspects of the sculpture iconography, as some embodiment sculptures have special attributes as the identity of the figure being depicted. The embodiment sculptures discussed in this study are the embodiment sculptures of the Gayatri, Tribhuwanatunggadewi, and Suhita. This study aims to reveal the meaning of the embodiment sculptures’ special attributes and the relationship between these meanings and the figures depicted. Peirce’s semiotic study was employed in this study. Based on the semiosis on the sculpture attributes, it is found that Tribhuwanatunggadewi is a Shiva-Buddhist queen regnant. It is also found that Suhita implemented government politics and cultural policy during her reign, as well as strengthening information regarding the role of Gayatri and Tribhuwanatunggadewi as Makalamanggalya. This study contributes a novel finding which complements pre-existed studies on iconography. It also contributes a methodology novelty in that semiotic approach could be used to provide comprehensive data in archaeological study.